2015
DOI: 10.5455/jice.20141128051842
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of probiotic potential of yeasts isolated from traditional cheeses manufactured in Serbia and Croatia

Abstract: Aim:The aim of this study was to investigate the in vitro probiotic potential of dairy yeast isolates from artisanal cheeses manufactured in Serbia and Croatia.Materials and Methods:Twelve yeast strains isolated from artisanal fresh soft and white brined cheeses manufactured in Serbia and Croatia were used in the study. Survival in chemically-simulated gastrointestinal conditions, adherence to epithelial intestinal cells and proliferation of gut-associated lymphoid tissue (GALT) cells were evaluated.Results:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…Similarly, these isolates have shown strong adhesive property to human intestinal cells (Caco-2). This finding is in accordance with Zivkovic et al (2015), where the probiotic organism adhesion is more than 40 cells to intestinal cells (Caco-2).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, these isolates have shown strong adhesive property to human intestinal cells (Caco-2). This finding is in accordance with Zivkovic et al (2015), where the probiotic organism adhesion is more than 40 cells to intestinal cells (Caco-2).…”
Section: Discussionsupporting
confidence: 93%
“…Although the three tested yeasts tended to follow the same trend in both of the intestinal cell lines, they exhibited a lower percentage of adhesion to the mucus-producing cell line HT29-MTX. These results are in agreement with Zivkovic et al [ 10 ], who mentioned that, generally, yeasts isolated from traditional cheeses manufactured in Serbia and Croatia show better adhesion to the Caco-2 cell line than to the HT29-MTX. They suggested that the presence of mucin hinders the availability of the cells as receptors for yeasts.…”
Section: Resultssupporting
confidence: 92%
“…This strain has shown a beneficial effect on inflammatory bowel diseases such as Crohn’s disease [ 8 ] by impacting the inflammatory cytokine production of the intestinal epithelial cells [ 9 ]. Little is known about the interaction between non- Saccharomyces yeasts and the human microbiota, but other yeast species have been reported to have potential probiotic properties, including Debaryomyces hansenii , Kluyveromyces lactis , Yarrrowia lipolytica , and Issatchenkia occidentalis [ 10 , 11 , 12 ]. These species are frequently associated with dairy products such as raw-milk cheeses [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a short history of application of yeast probiotics in human medicinecompared to other probiotic microorganisms such as lactic acid bacteria and Bifidobacteriumwas not enough for in-depth exploration of their safety attributes in the host (Soccol et al 2010). An increasing number of studies have been suggested various yeast species as potential probiotics for human and animals focusing on their health benefits; to this end, the systematic and rational evaluation of their virulence traits is of importance to reduce the future risks associated with yeast probiotics (Rima et al 2012;Zivkovi c et al 2015). A lack of probiotic yeast strains than bacterial strains reflects the scarcity of relevant studies, rather than the rarity of such yeasts (Czerucka et al 2007;Soccol et al 2010).…”
Section: Discussionmentioning
confidence: 99%